An Analysis of Remittance and Private Consumption in Nepal - Lamsal, Mani Ratna (Economic Journal of Nepal, 2023)
In recent decades, the increasing inflow of remittances and their benefits to originating countries have become an emerging issue in migration and development in the world economy. The government and household members of the country of origin have been taking the maximum possible advantages of remittances in various fields, and it is becoming a more stable source of external finance. However, around 80 percent of remittance received by households is used only for consumption purposes in Nepal. Despite the increasing importance of remittance in the Nepalese economy, the relationship between remittance and private consumption has not yet been adequately studied. Hence, the prime objective of this paper is to analyze the effects of remittance on private consumption expenditure in Nepal. The ARDL bounds testing model is employed in the study to identify the effects of remittance on private consumption in Nepal. The time series data for 20 years, 2001-2020, are collected from various government sources, such as the Ministry of Finance, Nepal Rastra Bank (NRB), and the National Statistics Office. This study finds a positive and significant relationship between remittances and private consumption in Nepal. The impact of other control variables like GDP is positive and significant for consumption. However, the consumer price index has a negative effect on consumption. The Nepal government and other concerned agencies should encourage sending remittances only from formal banking channels that could help with capital formation and thereby investment and job creation in Nepal. It also solves the liquidity crisis and foreign exchange constraints in the nation.